53 Low-grade isolated blunt paediatric solid organ injury and secondary overtriage in washington state 2005–2014. (19th September 2017) - Tessler, Robert A; Lyons, Vivian H; Hagedorn, Judith C; Vavilala, Monica S; Goldin, Adam; Arbabi, Saman; Rivara, Frederick P
Abstract : Statement of purpose: The Washington State Paediatric Transfer Guidelines list 'significant blunt injury to the chest or abdomen' as anatomic criteria for transfer. These guidelines also recommend transfer for any patient that may benefit from a paediatric trauma centre or paediatric ICU care. Data to guide these recommendations in isolated blunt solid organ injury are limited. Methods: Isolated blunt spleen, liver, and kidney injuries with abdominal Abbreviated Injury Severity Scores<=3 for patients under 16 during the years 2000–2014 from the Washington State Trauma Registry were analysed. Procedures, admission to ICU, transfusions, length of stay, and survival to discharge were considered. Results: One thousand, one hundred seventy-seven patients had an isolated abdominal solid organ injury of which 351 (29.8%) were transferred to a level I or II trauma centre. Sixty-three percent (222/351) were discharged in <72 hours. Two hundred and nine patients were admitted to the ICU, however 83.3% of those patients were transferred out of the ICU in <24 hours. Only six patients underwent a major procedure (surgery or angioembolization). Ninety-nine patients had an Injury Severity Score greater than 9, and none were transfused. All 351 transferred patients survived to discharge. Conclusions: Few patients with low grade isolated abdominal solid organ injury need to be transferred and trauma systems should revise their transfer policies. Prevention of unnecessary transfers is an opportunity for cost savings in paediatric trauma. Significance and Contributions to Injury and Violence Prevention Science: Optimal regional trauma care in the future may include greater use of telemedicine, however, issues around hospital revenue and provider liability may be potential barriers. These data highlight one potential area for improving efficiency while maintaining patient safety.